Publish or perish: exploring nurse academicians’ perspectives on academic publishing - Mohan, Kalpana; Sharmila, Pauline; Sharma, Swati; Bahl, Heena; Umar, Mohammed; Barnes, Ann; Kawar, Ajay Jyotiram; Suhashini,; Subrahmanyam, Nidigantla (International Journal of Research in Medical Sciences, 2025)
Academic publishing is a vital component of nursing scholarship, essential for faculty promotion, knowledge dissemination, and international recognition. Despite its importance, nurse academicians face multiple challenges such as limited mentorship, heavy workloads, language barriers, and financial constraints that impede scholarly engagement. This study aimed to clarify the concept of nurse academicians’ perspectives on academic publishing using Walker and Avant’s eight-step concept analysis framework. A systematic literature search was conducted across PubMed, Scopus, CINAHL, and Web of Science for studies published between 2015 and 2024. Both MeSH terms and free-text keywords were used, and fifteen empirical studies met the inclusion criteria. Data were extracted and appraised using a 15-item quality checklist, with findings synthesized into defining attributes, antecedents, consequences, and empirical referents. Three key attributes emerged: motivational drivers (career advancement, scholarly identity), barriers (workload, language difficulties, financial constraints, predatory publishing), and facilitators (mentorship, institutional support, collaboration). Antecedents included research competence, supportive culture, and funding availability. Consequences encompassed enhanced productivity and recognition but also risks such as burnout and unethical practices. Empirical referents such as publication count, H-index, and faculty surveys provided measurable indicators. A model case illustrated how mentorship, motivation, and resources interact to shape publishing perspectives. In conclusion, this analysis distinguishes perspectives from mere productivity, offering conceptual clarity and practical insights. Strengthening mentorship, redistributing workloads, providing writing and language support, and ensuring financial assistance are crucial for enhancing scholarly publishing in nursing. These findings inform institutional policy, nursing education, and global research collaboration.